2009
DOI: 10.1002/jts.20439
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of posttraumatic stress disorder among adult survivors three months after the Sichuan earthquake in China

Abstract: The study investigated the symptoms of posttraumatic stress disorder (PTSD) and associated risk factors among adult survivors 3 months after the 2008 Sichuan earthquake in China. One thousand five hundred sixty-three earthquake survivors in two communities participated in the study. The prevalence of probable PTSD was 37.8% and 13.0%, respectively, in the two communities that were affected differently by the earthquake. The significant predictive factors for the severity of PTSD symptoms were female gender, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
101
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 35 publications
13
101
1
Order By: Relevance
“…The other research focus was the catastrophic Wenchuan earthquake measuring 8.0 on the Richter scale occurred in Sichuan province of southwest China. During the earthquake, 69,227 people were killed, 374,643 injured, 17,923 listed as missing, and about 4.8 million were left homeless [22]. The symptoms of posttraumatic stress disorder and associated risk factors were investigated among health care workers in earthquake-affected areas in southwest China.…”
Section: Mental Health Of Medical Staffs In Special Eventsmentioning
confidence: 99%
“…The other research focus was the catastrophic Wenchuan earthquake measuring 8.0 on the Richter scale occurred in Sichuan province of southwest China. During the earthquake, 69,227 people were killed, 374,643 injured, 17,923 listed as missing, and about 4.8 million were left homeless [22]. The symptoms of posttraumatic stress disorder and associated risk factors were investigated among health care workers in earthquake-affected areas in southwest China.…”
Section: Mental Health Of Medical Staffs In Special Eventsmentioning
confidence: 99%
“…Posttraumatic stress disorder (PTSD) and generalized anxiety are the most frequently reported post-trauma sequelae (Freedy, Shaw, Jarrell, & Masters, 1992;Gibbs, 1989;Horowitz, 1977;Najarian, Goenjian, & Pelcovitz, 2001;Pynoos et al, 1993;Rubonis & Bickman, 1991;Scott, Knoth, Beltran-Quiones, & Gomez, 2003). The psychopathological effect of the 2008 Wenchuan earthquake on survivors has also been investigated recently (e.g., Wang et al, 2009). However, little is known about whether residents inside and outside of the devastated areas have different levels of concerns about the impact of the disaster.…”
Section: )mentioning
confidence: 99%
“…Affected to disasters [26], less knowledge affected by lower education, previous psychiatric illness (depression, anxiety), loss of something important, older or younger age at trauma, less social support, degree of exposure to the disaster and low of using to coping, these risk factors shown in more than one study and from different areas, cultures and circumstances [27]- [31].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Furthermore, there are two studies found effect the Sichuan earthquake to develop PTSD by presented 9.4% to 45.5% of survivors that complained of PTSD [31] [38].…”
Section: Risk Factorsmentioning
confidence: 99%